Perception and Feasibility Study toward Mini Vocational School Under the Islamic Boarding School in East Java - Bagus Oktafian Abrianto, - (Science and Technology Publications, Lda, 2018)
Improving the quality of human resources is the attention of all parties, especially in the atmosphere of multidimensional crisis that occurs today, the community needs the support of various parties to face free competition. The Mini Vocational Program from Education Department of East Java Province in 2014 is to produce skilled work force and new business opportunity in facing era of ASEAN Economic Community especially in East Java. There are several types of business vocational training in Mini Vocational School, customized local potential, ranging from batik, convection, computer network engineering, processed products, industry, machinery, and so on. The purpose of this study was to examine the influence of perception and feasibility toward the existence of Mini Vocational School under the Islamic Boarding School in East Java and to know what factors of both perceptual variable and feasibility variable that can influence to the existence of Mini Vocational School. This research m (More)